Asbab al Ikhtilaf - Ahmad Deski; Efizal Anwar (STAI Darul Quran Payakumbuh, 2020)
Differences of opinion in the legal field as a result of research (ijtihad) did not need to be seen as the factor that enfeeble the position of Islamic law, instead, it could give provide concessions for the people. Differences opinion of the scholars that occurred in the early days of Islam taught the next generation how to respond the differences to prevent hostilities or conflicts that damage the friendship among Muslims. Along with the development of Islamic law in the next generation, differences of opinion actually lead to negative things that damage friendship. It was caused by the taqlid toward the certain opinions and blame the others opinion. In this article, the author will try to discuss the causes the differences of opinion among the mujtahid. The results of research and discussion can be concluded that: 1). Ikhtilaf in language is disagreement. According to Raghib al Isfahani ikhtilaf and mukhalafah are when someone takes a path that is not taken by others, both in attitude and in words. Because ikhtilaf in human opinion sometimes causes the conflict, this word was sometimes used as a metophor for the meaning of the dispute and debate. 2). The causes of differences of opinion were: differences in legal sources, differences in abilities and ways of understanding texts, and differences in linguistic methods in understanding texts